REPRESENTASI MATEMATIS SISWA SMA DENGAN GAYA KOGNITIF FIELD DEPENDENT DALAM MEMECAHKAN MASALAH MATEMATIKA - Maftuh, Moh. Syukron; Khofifa, Lutfia Nur (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
The purpose of this study is to describe the mathematical representation of senior high school students who have a field dependent cognitive style in solving mathematical problems on the material of the Three Variable Linear Equation System, so this research is a descriptive study using a qualitative approach. The subjects of this study were 2 students of SMA Negeri 1 Kedamean Gresik class X MIPA 1 who had a field dependent cognitive style. The data collection techniques used are cognitive style test (GEFT), Problem Solving Test (TPM) and interviews. The results of this study are the mathematical representation of high school students who have a field dependent cognitive style in solving mathematical problems at the stage of understanding the problem, making a settlement plan and carrying out a settlement. The subject has something in common, namely representing the problem symbolically. However, at the stage of re-examining the results of the completion of the field dependent subject, they represented verbally because the subject wrote down the results of their completion using written words, and gave their opinion through direct sentences